2015
DOI: 10.1557/adv.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

3D/4D Printing Hydrogel Composites: A Pathway to Functional Devices

Abstract: The past few years have seen the introduction of a number of 3D and 4D printing techniques used to process tough hydrogel materials. The use of 'color' 3D printing technology where multiple inks are used in the one print allows for the production of composite materials and structures that can further enhance the mechanical performance of the printed hydrogel. This article reviews a number of 3D and 4D printing techniques for fabricating functional hydrogel based devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Expansion and contraction shape-changing behaviors are based on a shape-memory cycle, which includes the usual programming and recovery steps for thermo-responsive SMPs. Bakarich et al [3] demonstrated expansion and contraction behaviors of linear free swelling and shrinking of a thermo-responsive hydrogel being immersed in cold and hot water (Fig. 17).…”
Section: Expansion and Contractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expansion and contraction shape-changing behaviors are based on a shape-memory cycle, which includes the usual programming and recovery steps for thermo-responsive SMPs. Bakarich et al [3] demonstrated expansion and contraction behaviors of linear free swelling and shrinking of a thermo-responsive hydrogel being immersed in cold and hot water (Fig. 17).…”
Section: Expansion and Contractionmentioning
confidence: 99%
“…Surface topography is the representation of local deviations of a surface from a flat plane. These features usually occur under compressive loading conditions [52] Expansion/contraction Bakarich et al [3] Raviv et al [42] Yu et al [56] "This mechanism is driven by a variety of expansion ratios between active and rigid materials, which consist of scalable, hydrophobic active materials and rigid materials [3] Waving Wu et al [54] Wave shape deformation could occur in bilayers with comparable stiffness and layer thickness through swelling/shrinkage mismatch in response to activation stimuli [6] Curling Tibbits et al [52] Curling deformation is enabled by a stress mismatch between rigid and active materials from their different swelling properties [52] several features altogether known as a "wave" which is a complex shape. This behavior was achieved using a change in the water temperature as the stimuli.…”
Section: Bendingmentioning
confidence: 99%
“…Hydrogels are the most widely used solvent-responsive Materials 2021, 14, 1383 2 of 18 SMP and swell in response to a water stimulus [18]. Both types of SMPs have been used in various 4D printing studies as a form of composite [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the chemical or physical cross-linked three-dimensional network and large amounts of water, hydrogels have been widely used in medical science, tissue engineering, soft robots, and soft actuators [ 1 , 2 , 3 , 4 , 5 ]. In order to ensure the application of functions of hydrogels and reduce the manufacturing cost, many studies have been focused on fabricating repairable hydrogels.…”
Section: Introductionmentioning
confidence: 99%